THE ANGLE OF VIEW. LITERATURE AND PHOTOGRAPHY IN THE WORKS OF LEOPOLD BUCZKOWSKI - Bukowiecka, Marta (Prace Polonistyczne, 2024)
The article compares Leopold Buczkowski’s photography and literature. Although they do not present similar themes or motifs, they have much in common: they are grounded in similar artistic principles, and use similar techniques and artistic conventions. Both in his photography and prose, Buczkowski experiments with various perspectives. These types of works are based on the principle of anti-aestheticism and feature elements of pure nonsense. Developing his art, Buczkowski gradually moves away from documentary realism and probability, and places more and more emphasis on individual creative expression. He draws attention to the invisible, the atypical, and the unexpected, and thus plays with the conventions of presenting reality in photography.